Strong convergence theorems of a modified ishikawa iterative algorithm with errors for nonexpansive mappings - Liu, C.; Liu, Lishan (Kexue Chubanshe, 2016)
© 2016, Chinese Academy of Sciences. All right reserved.Under some suitable conditions, we introduce a new modified Ishikawa iterative algorithm with errors for converging strongly to a common element of the set of common fixed points of infinite family of nonexpansive mappings in a reflexive Banach space. The results presented here improve and generalize some known results and an example is given to demonstrate the application of our main results.